2017
DOI: 10.1080/17461391.2017.1347963
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical activity, fitness, physical complaints and BMI in German adults – results of a longitudinal study

Abstract: A general positive development regarding the amount of physical activity could be detected. However, if it is only an unsystematic increase of physical activity, this is not in itself enough to achieve health benefits. The strengthening of fitness should be focused when increasing physical activity, since only then a health benefit is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 40 publications
7
36
0
11
Order By: Relevance
“…For example, the second youngest group (30-44 years) had lower APR, when contrasted with their older counterparts (≥ 45 years). The increased physical activity among older populations is consistent with German research -especially for women [32]. While the causes of this are yet to be fully established, it might be that older German adults are better informed and more aware of health benefits of physical activity.…”
Section: 0%) In Contrast Lower Mvpa-mse Guideline Adherence Estisupporting
confidence: 72%
See 1 more Smart Citation
“…For example, the second youngest group (30-44 years) had lower APR, when contrasted with their older counterparts (≥ 45 years). The increased physical activity among older populations is consistent with German research -especially for women [32]. While the causes of this are yet to be fully established, it might be that older German adults are better informed and more aware of health benefits of physical activity.…”
Section: 0%) In Contrast Lower Mvpa-mse Guideline Adherence Estisupporting
confidence: 72%
“…This may positively influence being active especially among older populations who are perceiving health problems. Additionally, children leave the parental home (empty-nest-phase), so especially women have more time resources and sports clubs in Germany offer several activities, which are tailored to women [32]. Clearly, more research is needed to first, replicate this finding in prospective studies, and second, to determine its causes, especially for the decrease of physical activity in the younger age group.…”
Section: 0%) In Contrast Lower Mvpa-mse Guideline Adherence Estimentioning
confidence: 99%
“…A strong association between body mass index (BMI) and obesity has been documented (23). The WHO defined overweight as a BMI of 25-29.9 kg/m 2 and obesity as a BMI of 30 kg/m 2 or greater (24). In 15 patients with lower T2 signal intensity, we found that 10 patients (66.7%) showed a BMI of >25 kg/m 2 , and 3 patients (20%) showed a BMI of >30 kg/m 2 .…”
Section: █ Discussionmentioning
confidence: 99%
“…One of the commonly used parameters to measure subjective PA intensity is by using the International Physical Activity Questionnaire (IPAQ). [12][13][14] This is an instrument designed for adults and has been tested in adults aged 15-69 years old. Nevertheless, it is not recommended to use IPAQ for older and younger age groups..…”
Section: Introductionmentioning
confidence: 99%
“…17 Many studies have found that physical activities have a mild to a moderate correlation with the aerobic capacity. [12][13][14] Physical activities may relate to the quality of life (QoL), through good endurance in doing daily activities. The QoL is the subjective reflects from an individual's overall perception and satisfaction in their life or, in other word it is the overall enjoyment of life.…”
Section: Introductionmentioning
confidence: 99%